2014
DOI: 10.1061/(asce)te.1943-5436.0000675
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Entry Capacity for Single-Lane Modern Roundabouts: Case Study in Queensland, Australia

Abstract: Single-lane modern roundabouts are one of the most important intersection types in suburbs of Australia. It is therefore important to estimate their entry capacities. In this case study, we firstly propose an analytical model based on the gap acceptance theory by incorporating the effects of the exiting vehicles. It then proceeds to carry out a scenario analysis to assess the effects of the exiting indicators. This is followed by the discussions of the applicability of the proposed model. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Several studies have examined the capacity of roundabouts. Qu et al [9] estimated the entry capacity of single lane modern roundabout using a case study in Queensland. Sisiopiku and Oh [10] compared the performance of a roundabout with a four-leg intersection.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the capacity of roundabouts. Qu et al [9] estimated the entry capacity of single lane modern roundabout using a case study in Queensland. Sisiopiku and Oh [10] compared the performance of a roundabout with a four-leg intersection.…”
Section: Introductionmentioning
confidence: 99%
“…HCM 2000 model treat the exiting vehicles as non-existent, which are not counted as circulating traffic. Based on survey of 19 single-lane modern roundabouts in Queensland, Australia, Qu et al (2014) indicated that waiting vehicles will immediately (in an average of 1.4 seconds) enter the roundabout after exiting vehicles turn their indicators on (usually more than 1 second before the actual turning movements) [2]. In other words, a waiting vehicle might not necessarily wait for a critical gap if an exiting vehicle shows up.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study indicates that HCM 2000 model performs well under low to mid traffic conditions while it underestimates the capacities under high traffic conditions in combination with high proportions of exiting vehicles. [2]. In this paper, the two models are integrated using a scenario based approach to analyse the effects of not only exiting vehicles but also HGVs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations